Influence of openings on the snowdrift characteristics of cubes - Xintong Jiang; Hanbo Cui; Shenghao Guo; Zongyun Mo (PLoS ONE, 2025)
Snow drifts and accumulates under wind actions, leading to a complex distribution of snow around and on the surface of structures with openings, which in turn has a detrimental influence on the structures. There is no relevant code provision for this situation. Therefore, a wind tunnel study was carried out to experimentally investigate how opening size and vertical location (for cubes with single openings) and how the relative positions of different openings (for cubes with multiple openings) influenced the wind-induced snowdrifts around and on the surface of cubes with openings. A roughness coefficient was introduced to characterize the snow around cubes. It was found that snow accumulation at the side of the cube produced a greater uneven snow load. The number and vertical location of openings were the main factors influencing the roughness of the snow. The snow depth coefficient (Cs) around and on the surface of a cube is approximately negatively correlated with opening size and approximately positively correlated with opening vertical location. The simultaneous existence of openings on the windward, side and top faces of a cube adversely affected the safety of the surroundings of the cube. The variation pattern of fractal characteristic of particles, D, was similar to that of Cs when the snow was fully eroded at the windward corner of the cube. These findings will help improve the accuracy of snow distribution pattern prediction and enhance the safety and rationality of the structural design of buildings.